BUTTS, BOOKS, BUSES, AND BETTER INSTRUCTION: HOW A PRINCIPAL CAN DEVELOP ASSISTANT PRINCIPALS INTO EQUITY-CENTERED INSTRUCTIONAL LEADERS BY JUGGLING TASKS TOGETHER - Mudd, Timothy W (East Carolina University, 2023)
The study aimed to build the capacity of assistant principals to identify and support teachers in using equitable classroom practices. The Participatory Action Research (PAR) study in a rural North Carolina school district included a team of the principal and two assistant principals as co-practitioner researchers (CPR) to study how the principal could develop the knowledge and skills of the assistant principals to become equity-centered instructional leaders. Findings from the study reveal that principals can develop the knowledge and skills of assistant principals to become equity-centered instructional leaders by creating specific conditions and spaces, making the development of the assistant principal a priority, and juggling tasks with the assistant principal. Additionally, this study provides insight into how principals can intentionally work with assistant principals to simultaneously become better at conducting classroom observations, engaging teachers in post-observation coaching conversations, and ultimately becoming better equity-centered leaders. Throughout three inquiry cycles, the CPR group utilized the plan, do, study, act cycle of inquiry and pushed against the current practice of assistant principals' focus on "butts, books, and buses." In addition, we utilized Community Learning Exchange axioms and pedagogies (Guajardo et al., 2016), created Assistant Principal-Networked Improvement Communities (Bryk et al., 2015), engaged in classroom observations using the Calling-On Observation Tool, and engaged teachers in post-observation coaching conversations as we studied how a principal can help assistant principals become equity-centered instructional leaders.
Keywords: Principal; Assistant Principal Development; Leadership Development; Equity-Centered Instructional Leadership; Assistant school principals--In-service training--North Carolina; Educational equalization; Educational leadership; Rural schools--North Carolina